Uncovering near-free platinum single-atom dynamics during electrochemical hydrogen evolution reaction - Fang, Shi; Zhu, Xiaorong; Liu, Xiaokang; Gu, Jian; Liu, Wei; Wang, Danhao; Zhang, Wei; Lin, Yue; Lu, Junling; Wei, Shiqiang; Li, Yafei; Yao, Tao (Nature communications, 2020)
Single-atom catalysts offering intriguing activity and selectivity are subject of intense investigation. Understanding the nature of single-atom active site and its dynamics under working state are crucial to improving their catalytic performances. Here, we identify at atomic level a general evolution of single atom into a near-free state under electrocatalytic hydrogen evolution condition, via operando synchrotron X-ray absorption spectroscopy. We uncover that the single Pt atom tends to dynamically release from the nitrogen-carbon substrate, with the geometric structure less coordinated to support and electronic property closer to zero valence, during the reaction. Theoretical simulations support that the Pt sites with weakened Pt–support interaction and more 5 d density are the real active centers. The single-atom Pt catalyst exhibits very high hydrogen evolution activity with only 19 mV overpotential in 0.5 M H 2 SO 4 and 46 mV in 1.0 M NaOH at 10 mA cm −2 , and long-term durability in wide-pH electrolytes. Understanding the structural dynamics of single-atom site in electrochemical reactions is crucial for design of an efficient catalyst. Here, the authors develop highly active Pt single-atom electrocatalyst, and reveal the dynamic evolution of active sites by using operando synchrotron spectroscopy.